(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, employment of war disabled people, working conditions and problems in it, examination of medical labor expert commissions for those who have lost their health and become disabled, commission activity and its shortcomings, as well as vocational retraining of disabled people and their alternative work the issues of provision are analyzed.